Cigarette filter material, preparation method thereof and cigarette filter stick
By using a combination of carbon-based nano-adsorbent and modified smoke fibers in cigarette filter rods, the problems of powder removal and industrial application of nano-powder materials are solved, and the effects of high adsorption ratio and high absorption rate of hazardous components are achieved. Significantly reduces harmful substances inhaled by smokers.
Patent Information
- Application Number
- CN202411589642.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
Existing cigarette filter rods are prone to powder loss after adding nano powder materials, and are difficult to achieve industrial application. They cannot effectively reduce the harm of harmful substances in the flue gas, and at the same time affect the taste of smokers.
Using a combination of carbon-based nano-adsorbent and modified smoke fibers, the carbon-based nano-adsorbent consists of activated carbon fibers loaded with graphene oxide and nanominerals. The modified smoke fibers are treated by gel modification, combining alcohol solvents and super Critical carbon dioxide drying technology prepares cigarette filter materials with high adsorption ratio and high absorption rate of hazardous components.
The high adsorption ratio of cigarette filter materials and the high absorption rate of hazardous components are achieved, while almost no powder is lost, which significantly reduces the harmful substances inhaled by smokers and improves the safety and taste of cigarettes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tobacco, and in particular to a cigarette filter material and a preparation method thereof, and a cigarette filter rod. Background Art
[0002] In recent years, with the sharp increase in health problems caused by smoking, the tobacco industry is moving towards the direction of "low tar, low harm", and this requires a new material to achieve. Among them, adding nanomaterials with adsorption function to cigarette filter rods is an important research direction, which can reduce the harm of harmful substances in smoke to smokers without losing the taste. However, after adding nano powder materials to cigarette filter rods, they are easy to enter the smoker's mouth with the smoke, causing new safety hazards. At the same time, nano powder materials are also difficult to achieve industrialization, which seriously restricts the application of nano powder materials in cigarette filter rods.
[0003] Patent CN113841926A discloses a cigarette filter rod, which includes a first structure and a second structure, wherein the first structure is formed of a composite filter material, the second structure is formed of tobacco fibers, one end of the first structure is connected to the second structure, and the other end can be connected to a tobacco portion. The cigarette filter rod provided by the invention sheds powder and cannot guarantee the taste of smokers.
[0004] Therefore, it is necessary to provide a cigarette filter rod that can overcome the above-mentioned defects. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a cigarette filter material. The cigarette filter material provided by the present invention has the advantages of high adsorption rate, high absorption rate of harmful components and no powder falling.
[0006] The present invention provides a cigarette filter material, comprising a carbon-based nano-adsorbent and modified tobacco fiber;
[0007] The weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.2-0.8:3-4;
[0008] The carbon-based nano-adsorbent is an activated carbon fiber loaded with graphene oxide and nano-minerals;
[0009] The modified tobacco fiber is a tobacco fiber modified by gel.
[0010] Preferably, the preparation method of the carbon-based nano-adsorbent is:
[0011] The nano minerals and water are used to prepare a nano mineral suspension;
[0012] The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers, and then dried to obtain the carbon-based nano-adsorbent.
[0013] Preferably, the weight ratio of graphene oxide, nano-mineral and activated carbon fiber in the carbon-based nano-adsorbent is 0.01-0.2:0.1-3:100.
[0014] Preferably, the nano mineral is a non-metallic mineral of the aluminosilicate class; the non-metallic mineral of the aluminosilicate class includes zeolite, montmorillonite, sepiolite, medical stone or attapulgite; the activated carbon fiber is a fiber material with a particle size of 0.5 to 2 mm.
[0015] Preferably, the preparation method of the modified tobacco fiber comprises:
[0016] Dispersing polyglutamic acid and xylan in water, and using a strong base as a catalyst to perform a polycondensation reaction to obtain a polycondensation product mixed solution;
[0017] The tobacco fiber is added into the mixed solution of the polycondensation product, mixed and dispersed, left to stand for 1 to 2 hours, and dried and solidified to obtain the modified tobacco fiber.
[0018] Preferably, the mass ratio of the strong base, polyglutamic acid, xylan and tobacco fiber is 1:2-4:2-4:200-225.
[0019] And / or, the strong base is sodium hydroxide or potassium hydroxide;
[0020] and / or, the polycondensation reaction temperature is 40-50° C., and the reaction time is 2-4 hours;
[0021] And / or, the tobacco fiber is selected from at least one of acetate fiber, lactic acid fiber, polyimide fiber and polypropylene fiber.
[0022] The present invention provides a method for preparing a cigarette filter material according to any one of the above technical solutions, comprising:
[0023] The carbon-based nano-adsorbent and the modified tobacco fiber are stirred and mixed in an alcohol solvent, and then dried with supercritical carbon dioxide to obtain the product.
[0024] Preferably, the parameters of supercritical carbon dioxide drying include:
[0025] At a temperature of 35-45°C and a pressure of 10MPa-16MPa, at least a portion of the alcohol solvent is released every 10-30 minutes until no more of the alcohol solvent is released, and pressure relief treatment is performed, wherein the pressure is reduced to 0 within no more than 2 hours.
[0026] The alcohol solvent is selected from at least one of methanol, ethanol, n-butanol and isopropanol.
[0027] The present invention provides a cigarette filter rod, comprising the cigarette filter material described in any one of the above technical solutions or the cigarette filter material prepared by the preparation method described in any one of the above technical solutions.
[0028] The present invention provides a cigarette, comprising the cigarette filter rod described in the above technical solution.
[0029] Compared with the prior art, the present invention provides a cigarette filter material, including a carbon-based nano-adsorbent and a modified tobacco fiber; the weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.2~0.8:3~4; the carbon-based nano-adsorbent is an activated carbon fiber loaded with graphene oxide and nano-minerals; the modified tobacco fiber is a gel-modified tobacco fiber. The present invention uses a carbon-based nano-adsorbent as an adsorbent added to the tobacco fiber, and uses a gel-modified tobacco fiber. The gel component wrapped on the surface of the tobacco fiber helps to combine with the carbon-based nano-adsorbent to avoid the problem of powder falling. The activated carbon fiber loaded with graphene oxide and nano-minerals at the same time shows excellent harmful gas absorption effect. DETAILED DESCRIPTION
[0030] The present invention provides a cigarette filter material and a preparation method thereof and a cigarette filter rod. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the desired results. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art and they all fall within the scope of protection of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to achieve and apply the technology of the present invention.
[0031] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0032] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0033] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0034] The present invention provides a cigarette filter material, comprising a carbon-based nano-adsorbent and modified tobacco fiber;
[0035] The weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.2-0.8:3-4;
[0036] The carbon-based nano-adsorbent is an activated carbon fiber loaded with graphene oxide and nano-minerals;
[0037] The modified tobacco fiber is a tobacco fiber modified by gel.
[0038] The cigarette filter material provided by the present invention comprises a carbon-based nano-adsorbent and a modified tobacco fiber. The weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.2-0.8:3-4; in some embodiments, the weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.4-0.6:3-4; in some embodiments, the weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.55:3.6.
[0039] The carbon-based nano-adsorbent of the present invention is activated carbon fiber loaded with graphene oxide and nano-minerals.
[0040] According to the present invention, the preparation method of the carbon-based nano-adsorbent is:
[0041] The nano minerals and water are used to prepare a nano mineral suspension;
[0042] The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers, and then dried to obtain the carbon-based nano-adsorbent.
[0043] Mixing graphene oxide with water to prepare a graphene oxide aqueous solution;
[0044] Mixing the nano minerals with water to prepare a nano mineral suspension;
[0045] The activated carbon fiber of the present invention is pretreated before use, and the pretreatment steps include: the activated carbon fiber is boiled in water for 5 to 20 minutes and then dried, and pre-activated to remove impurities and moisture in the fiber.
[0046] The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated activated carbon fibers, and then dried to obtain the carbon-based nano-adsorbent; the present invention does not limit the specific steps and operations of the spraying, which are well known to those skilled in the art.
[0047] According to the present invention, the weight ratio of graphene oxide, nano-mineral and activated carbon fiber in the carbon-based nano-adsorbent is 0.01-0.2: 0.1-3: 100. Preferably, the weight ratio of graphene oxide, nano-mineral and activated carbon fiber is 0.05-0.1: 0.5-1: 100, further preferably, the weight ratio of graphene oxide, nano-mineral and activated carbon fiber is 0.08-0.1: 0.8-1: 100, and most preferably, the weight ratio of graphene oxide, nano-mineral and activated carbon fiber is 0.09: 0.86: 100.
[0048] In the present invention, the nano mineral is a non-metallic mineral of aluminosilicate; the non-metallic mineral of aluminosilicate includes zeolite, montmorillonite, sepiolite, medical stone or attapulgite; preferably sepiolite. The activated carbon fiber is a fiber material with a particle size of 0.5 to 2 mm; specifically, it can be 0.5 mm, 1 mm, 1.5 mm or 2 mm; or a range between any two of the above.
[0049] The nano mineral material added in the present invention has large specific surface area and adsorption capacity, and its pore size and surface chemical properties are controllable. It utilizes catalytic cracking to reduce carcinogens in cigarette smoke and has selective removal performance and mechanism for polycyclic aromatic hydrocarbons and nitrosamines in cigarette smoke.
[0050] In the present invention, as a preferred embodiment, the nano mineral is sepiolite, and a sepiolite suspension is applied to an acetate fiber bundle to make a qualified filter rod sample. The unique microstructural properties of the alternating arrangement of sepiolite chain layer units and pores can be used to selectively remove CO and other large molecular polar substances in cigarette smoke, and less non-polar compounds such as cigarette flavor are adsorbed, thereby maintaining the original smoking style of the cigarette.
[0051] According to the present invention, the method for preparing the modified tobacco fiber comprises:
[0052] Dispersing polyglutamic acid and xylan in water, and using a strong base as a catalyst to perform a polycondensation reaction to obtain a polycondensation product mixed solution;
[0053] The tobacco fiber is added into the mixed solution of the polycondensation product, mixed and dispersed, left to stand for 1 to 2 hours, and dried and solidified to obtain the modified tobacco fiber.
[0054] The present invention first disperses polyglutamic acid and xylan in water, and uses a strong base as a catalyst to perform a polycondensation reaction to obtain a polycondensation product mixed solution; the mass ratio of the strong base, polyglutamic acid, xylan and tobacco fiber is 1:2-4:2-4:200-225;
[0055] Preferably, the mass ratio of the strong base, polyglutamic acid, xylan and tobacco fiber is 1:3~4:3~4:210~220;
[0056] Further preferably, the mass ratio of the strong base, polyglutamic acid, xylan and tobacco fiber is 1:3.5:3.5:215;
[0057] And / or, the strong base is sodium hydroxide or potassium hydroxide;
[0058] And / or, the polycondensation reaction temperature is 40-50°C, and the reaction time is 2-4 hours; specifically, it can be 40°C, 42°C, 44°C, 46°C, 48°C or 50°C.
[0059] And / or, the tobacco fiber is selected from at least one of acetate fiber, lactic acid fiber, polyimide fiber and polypropylene fiber. Preferably, the tobacco fiber is selected from acetate fiber.
[0060] The reaction product of polyglutamic acid and xylan obtained by the present invention is in a gel state, wrapped on the surface of the tobacco fiber, plays a partial bonding role, helps to combine with the carbon-based nano adsorbent, and avoids powder loss. At the same time, the reaction product of polyglutamic acid and xylan has water absorption and swelling properties. After the filter tip is soaked during use, it forms a porous structure, and obtains better physical adsorption of harmful substances in cigarettes. In addition, the reaction product contains rich amino and hydroxyl groups, which are easy to hydrogen bond with phenolic and carbonyl harmful substances in cigarette smoke, and have an adsorption effect on these components.
[0061] The present invention provides a method for preparing a cigarette filter material according to any one of the above technical solutions, comprising:
[0062] The carbon-based nano-adsorbent and the modified tobacco fiber are stirred and mixed in an alcohol solvent, and then dried with supercritical carbon dioxide to obtain the product.
[0063] The preparation method of the cigarette filter material provided by the present invention firstly stirs and mixes the carbon-based nano adsorbent and the modified tobacco fiber in an alcohol solvent; the alcohol solvent is selected from at least one of methanol, ethanol, n-butanol and isopropanol.
[0064] The mass ratio of the carbon-based nano-adsorbent and the modified tobacco fiber is as described above, which will not be repeated here. The carbon-based nano-adsorbent and the modified tobacco fiber are immersed in the alcohol solution and stirred to mix uniformly.
[0065] After adding the alcohol solvent, the temperature is controlled at 45-50°C and the stirring and mixing time is 3-4 hours.
[0066] In the present invention, as a preferred embodiment, the CO2 supercritical drying step includes: at a temperature of 35-45°C and a pressure of 10MPa-16MPa, releasing at least part of the alcohol solvent every 10-30 minutes until no alcohol solvent is released, and performing pressure relief treatment, wherein the pressure relief treatment satisfies the condition of reducing the pressure to 0 within a time not exceeding 2 hours. This preferred case has a higher drying efficiency, and the prepared composite filter material has a smaller shrinkage rate and better elastic properties.
[0067] The present invention provides a cigarette filter rod, comprising the cigarette filter material described in any one of the above technical solutions or the cigarette filter material prepared by the preparation method described in any one of the above technical solutions.
[0068] The present invention provides a method for preparing a cigarette filter rod:
[0069] The composite filter material is cut into tows, and then filter rods are formed, which are then wrapped with cigarette paper to obtain cigarette filter rods.
[0070] The present invention does not limit the specific methods of cutting and wrapping, which are well known to those skilled in the art.
[0071] The cigarette filter rod obtained by the invention hardly sheds powder and greatly reduces harmful components in smoke.
[0072] The present invention provides a cigarette, comprising the cigarette filter rod described in the above technical solution. The present invention does not limit the other raw materials of the above cigarette, which are well known to those skilled in the art.
[0073] The composite filter material provided by the present invention has the advantages of high adsorption ratio, high absorption rate of harmful components and no powder falling. The present invention uses carbon-based nano-adsorbent as an adsorbent added to tobacco fiber. In order to solve the problem of powder falling, gel-modified tobacco fiber is used. The gel component wrapped on the surface of the tobacco fiber helps to combine with the carbon-based nano-adsorbent to avoid the problem of powder falling. The activated carbon fiber loaded with graphene oxide and nano-minerals at the same time shows excellent harmful gas absorption effect. On the one hand, graphene oxide is evenly loaded on the surface of the activated carbon fiber, and the surface active sites are increased, which has good selective adsorption for phenol, hydrogen cyanide and aldehydes and ketones. On the other hand, nano-mineral materials are compounded to increase the specific surface area and adsorption capacity, and the catalytic cracking effect is used to reduce carcinogens in cigarette smoke, which helps to selectively remove polycyclic aromatic hydrocarbons and nitrosamines in smoke. Performance and mechanism. In addition, the gel product formed by the reaction of polyglutamic acid and xylan is water-swellable and rich in amino and hydroxyl groups. When the filter tip is soaked during use, it has better physical adsorption capacity for harmful substances in cigarettes and is easier to hydrogen bond with phenols and carbonyl harmful substances in cigarette smoke, and has an adsorption effect on these components, so that the final cigarette filter rod has almost no powder shedding, and the harm of smoking is lower, so it can be used to prepare high-end cigarette products.
[0074] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0075] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0076] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0077] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0078] Some cases are recorded in the embodiments and comparative examples of the present invention, wherein the embodiments show certain implementation modes of the present invention. However, this does not mean that the effects of the present invention can only be achieved in these cases.
[0079] In order to further illustrate the present invention, the cigarette filter material and the preparation method thereof and the cigarette filter rod provided by the present invention are described in detail below in conjunction with the embodiments.
[0080] Unless otherwise specified, room temperature in the present invention means 25±5°C.
[0081] Preparation Example 1
[0082] The carbon-based nano-adsorbent A1 was prepared as follows:
[0083] (1) Prepare the raw materials according to the following ratio: the weight ratio of graphene oxide (JC Nano, nanometer grade), nano mineral sepiolite (Ron, R055265) and activated carbon fiber (1 mm thickness) is 0.09:0.86:100;
[0084] (2) Pretreatment of activated carbon fibers: The activated carbon fibers are boiled in water for about 15 minutes and then dried to perform pre-activation treatment to remove impurities and moisture from the fibers;
[0085] (3) Mixing graphene oxide with water (mass-volume ratio of 1 g:100 ml) to prepare a graphene oxide aqueous solution, and mixing nano-mineral with water (mass-volume ratio of 1 g:150 ml) to prepare a nano-mineral suspension;
[0086] (4) The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers according to the mass ratio, and then dried at 60°C to obtain a carbon-based nano-adsorbent.
[0087] Comparative Preparation Example 1
[0088] Compared with Preparation Example 1, graphene oxide was not added, and the remaining steps were the same as those in Preparation Example 1, that is, the carbon-based nano-adsorbent C1 was prepared according to the following method:
[0089] (1) Prepare the raw materials according to the following ratio: the weight ratio of nano mineral sepiolite (Ron, R055265) to activated carbon fiber (1 mm thickness) is 0.86:100;
[0090] (2) Pretreatment of activated carbon fibers: The activated carbon fibers are boiled in water for about 15 minutes and then dried to perform pre-activation treatment to remove impurities and moisture from the fibers;
[0091] (3) Mix the nano-mineral with water (mass-to-volume ratio of 1 g:150 ml) to prepare a nano-mineral suspension;
[0092] (4) Spray the nano-mineral suspension onto the activated carbon fiber according to the mass ratio, and then dry it at 60°C to obtain the carbon-based nano-adsorbent.
[0093] Comparative Preparation Example 2
[0094] Compared with Preparation Example 1, no nano minerals were added, and the remaining steps were the same as those of Preparation Example 1, that is, the carbon-based nano-adsorbent C2 was prepared according to the following method:
[0095] (1) Prepare the raw materials according to the following ratio: the weight ratio of graphene oxide (JC Nano, nanometer grade) to activated carbon fiber (1 mm thickness) is 0.09:100;
[0096] (2) Pretreatment of activated carbon fibers: The activated carbon fibers are boiled in water for about 15 minutes and then dried to perform pre-activation treatment to remove impurities and moisture from the fibers;
[0097] (3) Mixing graphene oxide and water (mass volume ratio is 1 g: 100 ml) to prepare a graphene oxide aqueous solution;
[0098] (4) Spraying the graphene oxide aqueous solution onto the activated carbon fibers according to the mass ratio and drying at 60°C to obtain a carbon-based nano-adsorbent.
[0099] Preparation Example 2
[0100] The carbon-based nano-adsorbent A2 was prepared as follows:
[0101] (1) Prepare the raw materials according to the following ratio: the weight ratio of graphene oxide (JC Nano, nanometer grade), nano mineral zeolite (McLean, P815597) and activated carbon fiber (1 mm thickness) is 0.08:0.8:100;
[0102] (2) Pretreatment of activated carbon fibers: The activated carbon fibers are boiled in water for about 15 minutes and then dried to perform pre-activation treatment to remove impurities and moisture from the fibers;
[0103] (3) Mixing graphene oxide with water (mass-volume ratio of 1 g:100 ml) to prepare a graphene oxide aqueous solution, and mixing nano-mineral with water (mass-volume ratio of 1 g:150 ml) to prepare a nano-mineral suspension;
[0104] (4) The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers according to the mass ratio, and then dried at 60°C to obtain a carbon-based nano-adsorbent.
[0105] Preparation Example 3
[0106] The carbon-based nano-adsorbent A3 was prepared as follows:
[0107] (1) Prepare the raw materials according to the following ratio: the weight ratio of graphene oxide (JC Nano, nanometer grade), nano-mineral attapulgite (McLean, A921976) and activated carbon fiber (1 mm thickness) is 0.1:1:100;
[0108] (2) Pretreatment of activated carbon fibers: The activated carbon fibers are boiled in water for about 15 minutes and then dried to perform pre-activation treatment to remove impurities and moisture from the fibers;
[0109] (3) Mixing graphene oxide with water (mass-volume ratio of 1 g:100 ml) to prepare a graphene oxide aqueous solution, and mixing nano-mineral with water (mass-volume ratio of 1 g:150 ml) to prepare a nano-mineral suspension;
[0110] (4) The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers according to the mass ratio, and then dried at 60°C to obtain a carbon-based nano-adsorbent.
[0111] Preparation Example 4
[0112] The modified tobacco fiber B1 was prepared as follows:
[0113] (1) Prepare raw materials according to the following ratio: the mass ratio of sodium hydroxide, polyglutamic acid (CAS No. 25513-46-6), xylan (CAS No. 9014-63-5) and cellulose acetate is 1:3.5:3.5:215;
[0114] (2) dispersing polyglutamic acid in deionized water (mass volume ratio of 1 g: 150 ml), heating to about 45° C., and obtaining a polyglutamic acid aqueous solution;
[0115] (3) adding sodium hydroxide and xylan to the polyglutamic acid aqueous solution, reacting at 45° C. for about 3 hours and then cooling to room temperature to obtain a polyglutamic acid grafted xylan solution;
[0116] (4) The tobacco fiber is put into the polyglutamic acid grafted xylan solution, mixed evenly, left to stand for about 2 hours, and then placed in a dry environment at 100° C. for curing for 6 hours to obtain the modified tobacco fiber.
[0117] Preparation Example 5
[0118] The modified tobacco fiber B2 was prepared as follows:
[0119] (1) Prepare raw materials according to the following ratio: the mass ratio of sodium hydroxide, polyglutamic acid (CAS No. 25513-46-6), xylan (CAS No. 9014-63-5) and cellulose acetate is 1:3:3:210;
[0120] (2) dispersing polyglutamic acid in deionized water (mass volume ratio of 1 g: 150 ml), heating to about 40° C., and obtaining a polyglutamic acid aqueous solution;
[0121] (3) adding sodium hydroxide and xylan to the polyglutamic acid aqueous solution, reacting at 40° C. for about 4 hours and then cooling to room temperature to obtain a polyglutamic acid grafted xylan solution;
[0122] (4) The tobacco fiber is put into the polyglutamic acid grafted xylan solution, mixed evenly, left to stand for about 2 hours, and then placed in a dry environment at 100° C. for curing for 6 hours to obtain the modified tobacco fiber.
[0123] Preparation Example 6
[0124] Modified tobacco fiber B3 was prepared as follows:
[0125] (1) Prepare the raw materials according to the following ratio: the mass ratio of sodium hydroxide, polyglutamic acid (CAS No. 25513-46-6), xylan (CAS No. 9014-63-5) and cellulose acetate is 1:4:4:220;
[0126] (2) dispersing polyglutamic acid in deionized water (mass volume ratio of 1 g: 150 ml), heating to about 50° C., and obtaining a polyglutamic acid aqueous solution;
[0127] (3) adding sodium hydroxide and xylan to the polyglutamic acid aqueous solution, reacting at 50° C. for about 2 hours and then cooling to room temperature to obtain a polyglutamic acid grafted xylan solution;
[0128] (4) The tobacco fiber is put into the polyglutamic acid grafted xylan solution, mixed evenly, left to stand for about 2 hours, and then placed in a dry environment at 100° C. for curing for 6 hours to obtain the modified tobacco fiber.
[0129] Example 1
[0130] Prepare the composite filter material D1 as follows:
[0131] (1) Prepare raw materials according to the following ratio: the weight ratio of carbon-based nano-adsorbent A1 to modified tobacco fiber B1 is 0.55:3.6;
[0132] (2) The carbon-based nano-adsorbent and the modified tobacco fiber are added to ethanol and immersed, and stirred and dispersed evenly. The temperature is controlled at about 45°C and the stirring and mixing time is 4 hours. Then, at a temperature of 40°C and a pressure of 11.5 MPa, part of the ethanol is released every 15 minutes until no solvent is released. The pressure is reduced to 0 within 2 hours to obtain a composite filter material.
[0133] Example 2
[0134] The composite filter material D2 was prepared by the same method as in Example 1, except that the raw material composition was: the carbon-based nano-adsorbent A2 and the modified tobacco fiber B2 in a weight ratio of 0.4:3.
[0135] Example 3
[0136] The composite filter material D3 was prepared by the same method as in Example 1, except that the raw material composition was: the carbon-based nano-adsorbent A3 and the modified tobacco fiber B3 in a weight ratio of 0.6:4.
[0137] Example 4
[0138] The composite filter material D4 was prepared by the same method as in Example 1, except that the raw material composition was: the carbon-based nano-adsorbent A2 and the modified tobacco fiber B1 in a weight ratio of 0.45:3.5.
[0139] Example 5
[0140] The composite filter material D5 was prepared by the same method as in Example 1, except that the raw material composition was: the carbon-based nano-adsorbent A3 and the modified tobacco fiber B2 in a weight ratio of 0.55:4.
[0141] Example 6
[0142] The composite filter material D6 was prepared by the same method as in Example 1, except that the raw material composition was: the carbon-based nano-adsorbent A1 and the modified tobacco fiber B3 in a weight ratio of 0.6:3.8.
[0143] Comparative Example 1
[0144] The composite filter material E1 was prepared by the same method as in Example 1, except that the carbon-based nano-adsorbent A1 was replaced by an equal amount of carbon-based nano-adsorbent C1, and the rest were the same.
[0145] Comparative Example 2
[0146] The composite filter material E2 was prepared by the same method as in Example 1, except that the carbon-based nano-adsorbent A1 was replaced by an equal amount of the carbon-based nano-adsorbent C2, and the rest were the same.
[0147] Comparative Example 3
[0148] The composite filter material E3 was prepared by the same method as in Example 1, except that the carbon-based nano-adsorbent A1 was replaced with an equal amount of activated carbon fibers, and the rest were the same.
[0149] Comparative Example 4
[0150] The composite filter material E4 was prepared by the same method as in Example 1, except that the modified tobacco fiber B1 was replaced by an equal amount of acetate fiber, and the rest were the same.
[0151] Comparative Example 5
[0152] The composite filter material was prepared by the same method as in Example 1, except that the carbon-based nano-adsorbent A1 was directly replaced by an equal amount of graphene oxide, and the rest was the same.
[0153] Comparative Example 6
[0154] The composite filter material was prepared by the same method as in Example 2, except that the carbon-based nano-adsorbent A2 was directly replaced by an equal amount of nano-mineral zeolite, and the rest were the same.
[0155]
Product Testing
[0156] The composite filter materials D1-D6 and E1-E4 prepared in Examples 1-6 and Comparative Examples 1-4 were tested for powder loss rate and adsorption rate according to the following method.
[0157] Testing method for powder loss rate: weigh the mass m0 of the composite filter material sample, put it into a standard vibrating sieve machine, take it out after 2 minutes, weigh the mass m1 of the composite filter material sample after vibrating sieve, powder loss rate = (m0-m1) / m0*100%.
[0158] Adsorption rate test method: weigh the mass m0 of the composite filter material sample, then soak the composite filter material sample in white oil until the composite filter material sample reaches adsorption equilibrium, then take it out and weigh the mass m1 of the composite filter material sample after soaking. Adsorption rate = (m1-m0) / m0.
[0159] The composite filter materials prepared in the examples and comparative examples were cut into tows and then formed into filter rods, which were then wrapped with cigarette paper to obtain cigarette filter rods of corresponding specifications, and then made into cigarettes with tobacco. The total particulate matter, tar content and nicotine content of the mainstream smoke of the cigarettes were tested.
[0160] The preparation method of the cigarette is a conventional operation in the art, and is specifically prepared by referring to the following steps:
[0161] (1) 50 g of tobacco leaves and 100 g of tobacco stems purchased from Yunnan China Tobacco Industry Co., Ltd. were crushed into tobacco powder of 100-120 mesh at 40°C;
[0162] (2) the tobacco powder is mixed with sodium bicarbonate, potassium citrate, 10% tobacco white latex solution, propylene glycol and tobacco flavoring material in a mass ratio of 100:1:0.5:5:0.2:0.05 to obtain tobacco particles by one step granulation and drying, and particles smaller than 70 mesh are removed by air separation;
[0163] (3) Spraying polyethylene hot melt adhesive on the surface of the above-mentioned tobacco particles that have passed the air selection, pressing them into a cylindrical mold with a diameter of 7.5 mm from one end using a continuous feeding device under heat preservation conditions, and extruding them from the other end after solidification and rapid cooling to obtain tobacco particle round rods with a density of 0.3 g / mL;
[0164] (4) After the tobacco rod is extruded, it is wrapped with cigarette paper, cut into 59 mm lengths, and connected to the cigarette filter rod through tipping paper to form a cigarette.
[0165] The total particulate matter, tar content and nicotine content are tested according to the following methods:
[0166] Test method for total particulate matter: refer to the method for testing total particulate matter in cigarettes specified in GB / T19609-2004, Determination of total particulate matter and tar by conventional analytical smoking machine for cigarettes.
[0167] Test method for tar content: refer to the method for testing tar content of cigarettes specified in GB / T19609-2004 "Determination of total particulate matter and tar by conventional analytical smoking machine for cigarettes".
[0168] Test method for nicotine content: refer to the method for testing nicotine content in cigarettes specified in GB / T19609-2004 for the determination of total particulate matter and tar using a conventional analytical smoking machine for cigarettes.
[0169] The test results are shown in Table 1.
[0170] Table 1
[0171]
[0172] It can be seen from Table 1 that the cigarette filter rod provided by the embodiment of the present invention hardly sheds powder and poses no inhalation risk to smokers. The prepared cigarette filter has excellent adsorption effects on total particulate matter, tar, and nicotine in smoke and can significantly reduce the content of harmful substances. The product performance of the comparative example is not as good as that of the embodiment.
[0173] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A cigarette filter material, characterized in that: Including carbon-based nano-adsorbents and modified tobacco fibers; The weight ratio of the carbon-based nano-adsorbent to the modified tobacco fiber is 0.2-0.8:3-4; The carbon-based nano-adsorbent is an activated carbon fiber loaded with graphene oxide and nano-minerals; The modified tobacco fiber is a tobacco fiber modified by gel.
2. The cigarette filter material according to claim 1, characterized in that: The preparation method of the carbon-based nano adsorbent is: The nano minerals and water are used to prepare a nano mineral suspension; The graphene oxide aqueous solution and the nano-mineral suspension are sprayed onto the activated carbon fibers, and then dried to obtain the carbon-based nano-adsorbent.
3. The cigarette filter material according to claim 2, characterized in that: The weight ratio of graphene oxide, nano mineral and activated carbon fiber in the carbon-based nano adsorbent is 0.01-0.2:0.1-3:
100.
4. The cigarette filter material according to claim 2, characterized in that: The nano mineral is a non-metallic mineral of aluminosilicate; the non-metallic mineral of aluminosilicate includes zeolite, montmorillonite, sepiolite, medical stone or attapulgite; the activated carbon fiber is a fiber material with a particle size of 0.5-2 mm.
5. The cigarette filter material according to claim 1, characterized in that: The preparation method of the modified tobacco fiber comprises: Dispersing polyglutamic acid and xylan in water, and using a strong base as a catalyst to perform a polycondensation reaction to obtain a polycondensation product mixed solution; The tobacco fiber is added into the mixed solution of the polycondensation product, mixed and dispersed, left to stand for 1 to 2 hours, and dried and solidified to obtain the modified tobacco fiber.
6. The cigarette filter material according to claim 5, characterized in that: The mass ratio of the strong base, polyglutamic acid, xylan and tobacco fiber is 1:2-4:2-4:200-225. And / or, the strong base is sodium hydroxide or potassium hydroxide; and / or, the polycondensation reaction temperature is 40-50° C., and the reaction time is 2-4 hours; And / or, the tobacco fiber is selected from at least one of acetate fiber, lactic acid fiber, polyimide fiber and polypropylene fiber.
7. A method for preparing a cigarette filter material according to any one of claims 1 to 6, characterized in that: include: The carbon-based nano-adsorbent and the modified tobacco fiber are stirred and mixed in an alcohol solvent, and then dried with supercritical carbon dioxide to obtain the product.
8. The preparation method according to claim 7, characterized in that: The parameters of the supercritical carbon dioxide drying include: At a temperature of 35-45° C. and a pressure of 10 MPa-16 MPa, at least a portion of the alcohol solvent is released every 10-30 minutes until no more alcohol solvent is released, and a pressure relief treatment is performed, wherein the pressure is reduced to 0 within a period of no more than 2 hours; The alcohol solvent is selected from at least one of methanol, ethanol, n-butanol and isopropanol.
9. A cigarette filter rod, characterized in that: The invention comprises the cigarette filter material according to any one of claims 1 to 6 or the cigarette filter material prepared by the preparation method according to any one of claims 7 to 8.
10. A cigarette, characterized in that: The invention comprises the cigarette filter rod as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing polyglutamic acid hydrogel
CN101891954A
Grapheme type fiber cigarette filter and preparation method thereof
CN103005712A
Hydroxy propyl methyl cellulose (HPMC) modified cigarette filter tip prepared by polypropylene fiber and preparation method thereof
CN103110189A
Ternary composite filter stick containing cuprous ion-based MOFs-gel particles with CO specific adsorption capacity
CN111358050A
Cross-linked polyglutamic acid hydrogel and preparation method thereof
CN111635542A